ANALISIS PERBANDINGAN BIAYA PENGGUNAAN ALAT ANGKUT RDT TEREX TR60 DENGAN RDT EUCLID R60 PADA PENAMBANGAN OVERBURDEN DI PIT E UTARA PT. KARBINDO ABESYAPRADHI - Prismark Dhonald Mirzha; Murad Murad; Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2014)
In the overburden mining activities in the North Pit E,            PT. Karbindo Abesyapradhi using two brands about conveyance of rigid dump trucks Terex TR60 and Euclid R60 rigid dump truck. From the gained information, conveyance TR60 rigid dump truck is a new conveyance. While the conveyance Euclid R60 rigid dump truck is a long conveyance.Known to owning operating cost of conveyance Euclid R60 rigid dump truck US $ 93.63, while owning the operating cost conveyance of rigid dump trucks TR60 US $ 131.75. Then from the calculation of the productivity of the authors received, productivity Euclid R60 rigid dump truck better than productivity conveyance of rigid dump trucks Terex TR60. About productivity Euclid R60 rigid dump truck 56,796 BCM/h, while the productivity of rigid dump trucks Terex TR60 48,896 BCM/h.Then owning operating cost is divided by the productivity of the production cost to gain conveyance to determine which is more beneficial. And note the cost production of rigid dump trucks terex TR60 2,694 USD/BCM, while the cost production of rigid dump trucks Terex TR60 US $ 1,648. Based on the results gained, conveyance Euclid R60 rigid dump truck is more profitable than the conveyance of rigid dump trucks Terex TR60. And advised if the company wants to procure the means of conveyance. Better to choose Euclid R60 rigid dump truck. Key word : Owning Cost, Operating Cost, Productivity, Cost of Production